Kepuasan Siswa Terhadap Layanan Konseling Individual yang dilakukan Guru BK di SMA 6 Takengon - Desy, Desy Murni Lasari (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2023)
This research aims to determine the level of student satisfaction with individual counseling services provided by guidance and counseling teachers at SMAN 6 Takengon, both related to the personality of the guidance and counseling teachers and professional skills, supporting facilities and infrastructure, counseling services. This research includes quantitative research with an analytical survey approach. The population in this study were all students of SMA Negeri 6 Takengon, Central Aceh district, totaling 400 students. The sample was taken as many as 40 students using stratified random sampling technique. The instrument used is a Likert model scale. Then the data obtained was analyzed using descriptive analysis. The results of research on individual service factors obtained an average value of (3.37), which means that the majority of students expressed satisfaction with the individual counseling services provided by the guidance and counseling teachers at SMAN 6 Takengon. The majority of respondents answered that they were satisfied with a total score of 304. This indicates that overall both students and female students expressed their satisfaction with the individual counseling services provided by the guidance and counseling teachers at SMAN 6 Takengon. Both in terms of the implementer (Guidance and Counseling teacher), the facilities provided, as well as the time and opportunities for individual counseling services. The implementing aspect (Guidance and Counseling teacher) obtained the answer "Quite Satisfied" of 71 with a percentage of 8.88%. The Facilities Aspect obtained an answer of "Quite Satisfied" of 50 with a percentage of 6.25%. The time and opportunity aspects of the service obtained a "Satisfied" answer of 158 with a percentage of 19.75%. This indicates that the implementation aspect (Guidance and Counseling teacher), facilities and service times and opportunities satisfy the students.